The duality of reading and writing development in middle-school students - Preston, Kendra J. (Kansas State University, 2021)
This was a qualitative case study that focused on the discrepancy of literacy development at the middle school level of average students. The longitudinal case study expanded the course of one and a half academic years; beginning in August 2019 and concluding in January 2021. The study focused on two male participants who exhibited incongruent literacy development; therefore, one was categorized as a strong reader and poor writer, and the other was categorized as a strong writer and poor reader. The findings suggested that reading motivation is highly individualized, but was fostered prior to entering the school environment. Writing, however, was taught and reinforced in the school setting, but was deemed an enjoyable experience when it was creative in nature. Additionally, traditional measures of literacy proficiency, such as standardized assessments, do not accurately convey the whole picture as it contrasts the theoretical underpinnings suggested by Vygotsky and Piaget’s Social Constructivism. Thus, this study explored how to best support the literacy development of students at the middle school level in both the home and school setting.
Keywords: Literacy; Middle school; Reading; Writing; Discrepant literacy development